2011
DOI: 10.1105/tpc.111.085480
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Transport in Tobacco Leaf Epidermis Cells Involves a Single Route for Soluble Cargo and Multiple Routes for Membrane Cargo

Abstract: We tested if different classes of vacuolar cargo reach the vacuole via distinct mechanisms by interference at multiple steps along the transport route. We show that nucleotide-free mutants of low molecular weight GTPases, including Rab11, the Rab5 members Rha1 and Ara6, and the tonoplast-resident Rab7, caused induced secretion of both lytic and storage vacuolar cargo. In situ analysis in leaf epidermis cells indicates a sequential action of Rab11, Rab5, and Rab7 GTPases. Compared with Rab5 members, mutant Rab1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 90 publications
2
96
1
1
Order By: Relevance
“…During the preparation of this report, Batistič et al [46] reported that S-acylation of three cysteine residues in the Nterminus is required for vacuolar targeting of CBL2 in a Brefeldin A-insensitive pathway. Particularly relevant to this study, it was also shown that the CBL6-GFP chimera with a similar TTS at the N-terminus was targeted to tonoplast independently from the typical secretory pathway [47]. In other words, TTS is distinct from a typical signal peptide that mediates protein translocation through the secretory pathway.…”
Section: Discussionmentioning
confidence: 96%
“…During the preparation of this report, Batistič et al [46] reported that S-acylation of three cysteine residues in the Nterminus is required for vacuolar targeting of CBL2 in a Brefeldin A-insensitive pathway. Particularly relevant to this study, it was also shown that the CBL6-GFP chimera with a similar TTS at the N-terminus was targeted to tonoplast independently from the typical secretory pathway [47]. In other words, TTS is distinct from a typical signal peptide that mediates protein translocation through the secretory pathway.…”
Section: Discussionmentioning
confidence: 96%
“…However, GFP-VSR2(Y612A) accumulates to the TGN and GFP-BP80-Y612A trafficked to the plasma membrane Foresti et al, 2010). Moreover, a vacuolar cargo Aleu-RFP was trapped in the ER when COPIImediated ER export was inhibited by overexpression of Sec12 (Bottanelli et al, 2011). This alternative model was proposed based on the results of a study showing the localization of SNX2 at the TGN and redistribution of VSRs to the TGN in the presence of a mutant form of SNX (Niemes et al, 2010b).…”
Section: Vsr1 Recycles From the Pvc To The Tgn In Arabidopsis Mesophymentioning
confidence: 99%
“…The unique organization of endosomal trafficking in plants is also demonstrated by the observation that the trans-Golgi network (TGN) acts as an early endosome in plants (Dettmer et al, 2006;Lam et al, 2007;Viotti et al, 2010), from which multivesicular endosomes are proposed to be directly generated by maturation (Niemes et al, 2010;Scheuring et al, 2011). The RAB11 group (also known as RABA in Arabidopsis), which is localized to TGNrelated secretory compartments and is involved in cell plate formation and tip growth (Preuss et al, 2004;Chow et al, 2008;Szumlanski and Nielsen, 2009;Kang et al, 2011;Feraru et al, 2012;Asaoka et al, 2013;Berson et al, 2014;Kirchhelle et al, 2016), is also implicated in endosomal/vacuolar trafficking (Bottanelli et al, 2011;Choi et al, 2013). These lines of evidence indicate that endosomal trafficking in plant cells operates in a different manner from that in non-plant organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Canonical RAB5s and ARA6 are localized to distinct but overlapping populations of multivesicular endosomes Haas et al, 2007;Ebine et al, 2011), suggesting diversification of their functions. ARA6 acts in the endosome-to-plasma membrane trafficking pathway (Ebine et al, 2011) and may also be involved in a vacuolar trafficking pathway (Bottanelli et al, 2011). ARA7 and RHA1, in contrast, redundantly regulate endocytic and vacuolar trafficking pathways (Sohn et al, 2003;Kotzer et al, 2004;Dhonukshe et al, 2006;Ebine et al, 2011Ebine et al, , 2014Beck et al, 2012).…”
Section: Introductionmentioning
confidence: 99%